RETRACTED: Pengaruh Stres Kerja yang Dimoderasi Kecerdasan Emosional pada Kepuasan Kerja di Sebuah Hotel - Wiyaniti, Dewa Ayu Diah Oka; Widaharthana, I Putu Esa; Artajaya, Made (Stupa, 2024)
Research the Effect of Job Stress on Job Satisfaction Moderated by Emotional Intelligence took place at the Hilton Garden Inn Bali Ngurah Rai Airport. The purpose of this study is to find out whether there is a moderating role of the variable emotional intelligence on the relationship of work stress with job satisfaction. The methods of collecting data is through the questionnaires distribution to employees who are at the staff and supervisor level in Hilton Garden Inn Hotel Ngurah Rai Airport. There are 90 set of questionnaires distributed to the respondents. The techniques of analyzing data that used in this research are simple linear regression analysis and tiered linear regression analysis. The findings of this research shows that there is a significant effect caused by work stress on job satisfaction by 27.1% with the rest being other variables that not discussed in this research. Also in this study it was found that there is a moderating role in the emotional intelligence variable which can weaken the effect caused by work stress on job satisfaction as evidenced by the results of the t value = -3.003 <t table (0.05, 89) = -1.99.